String Teacher Preparation Programs in the United States. Issue 1 (July 2020) - Chang, Annalisa C.; Ammerman, Angela
The rise in demand for string teachers is a sign of support for string programs across the United States. Despite an increase in string teacher positions, there is growing concern regarding the lack of qualified string music education graduates to fill the vacancies, sometimes leading administrators to close programs. This study investigated the status of string teacher education programs in the United States. Participants for this study were degree-granting institutions ( N = 636) accredited by the National Association of Schools of Music (NASM). The NASM directory listings and institution websites were examined to determine what type of degrees were offered, and presence of a full-time string music education faculty member. Results indicated that while most NASM-accredited institutions offer some type of undergraduate degree in music education, very few institutions (16%) were shown to have a full-time string music education specialist. Results also indicated a significant relationship between the size of school and likelihood of having a full-time string music education specialist, χ 2 (7, N = 526) = 80.03, p < .001.